Reconstruction of memories and recognition of care work in 'Nedar' and 'A metamorfose dos pássaros' - Laura Caballero Rabanal (2i Revista de Estudos de Identidade e Intermedialidade)
Recently, Spanish and Portuguese female filmmakers have shown an increasing interest in reconstructing family memories and unveiling its secrets, being the third generation after the far-right dictatorships that ruled both Iberian countries during almost half of the past century. Francoism and Salazarism promoted a model of State and family based on the traditional nuclear family with strict gender roles. By analyzing two autoethnographic documentary films, Nedar (2008), by Catalan director Carla Subirana, and A Metamorfose dos Pássaros (2020), by Portuguese filmmaker Catarina Vasconcelos, whose protagonists are the creators’ grandmothers, this paper seeks to explore how these two films not only retrieve family and national memories, but also how they challenge the family patterns dictated by both dictatorships, placing life and care work at the center.